Hubungan Penguasaan Kosakata dengan Kemampuan Menulis Karangan Argumentasi Siswa Kelas XI IPS SMAN 1 Guguak 50 Kota - Rianti, Maya; Basri, Irfani; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study was (1) to describe the ability of vocabulary class XI student of SMAN 1 Guguak, (2) to describe the ability to write essays arguing Negeri1 high school students of class XI Guguak, (3) describe the relationship between vocabulary skills with the ability to write an argument essay graders XI SMA Negeri 1 Guguak. This research is quantitatively using descriptive. The population was 195 0rang as much in five local spread. The sample of this study were 30. The percentage of samples 15% of the total population of students per class. The data of this study in the form of objective test results for the multiple-choice vocabulary test consisting of 30 items about. Based on the analyzes of the data were performed, obtained the following results. First, the average level of vocabulary class XI student of SMAN 1 Guguak are in good qualification (82.66%) in the range of 76-85%. Second, the average ability of students to write essays arguing class XI SMA Negeri 1 Guguak be more than enough in qualifying (74.68%) in the range of 66-75%. Third, there is a significant positive relationship between relationship vocabulary with the ability to write an argument essay class XI student SMAN 1 Guguak, obtained t value of 9.07 is greater than the t table with degrees liberated (n-2) and a significant level of 95 % is equal to 1.701.